Media Convergence in Serambi Indonesia - Harisul Amal (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2022)
This study aims to explain the application of local media convergence in Serambi Indonesia in Aceh. This study uses a descriptive method with a qualitative approach. The technique of collecting data is by using interview, observation and documentation techniques. The results of this study indicate that Serambi Indonesia conducts convergence in various divisions, in the newsroom division, Serambi Indonesia applies an editorial room system with a single newsroom system, which has an impact on the effectiveness of journalists' work. With the convergence of content, Serambi Indonesia adapts to the platform it has. Serambi Indonesia recruits new journalists who understand their duties and roles and then provides them with various journalistic training to support the smooth running of their duties. The results of this study have an impact on strategies to improve media quality in the face of media business competition in the era of convergence.